2016
DOI: 10.1080/07373937.2016.1170028
|View full text |Cite
|
Sign up to set email alerts
|

Electrohydrodynamic drying of sand

Abstract: This study analyzes the electrohydrodynamic (EHD) drying characteristics of sand.Effect of process parameters (independent variables) including air speed, electrode gap and applied voltage on drying kinetics and dependent variables including percentage water removed (%), Sherwood number, EHD number and specific energy consumed (kJ·kg -1 ) were also investigated using a central composite design and response surface methodology. Maximum drying was obtained for process parameter combination of air speed (2 m·s -1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In contrast, 2×2 electrode initiated exponential drying kinetics (falling drying rate), which indicates diffusion-limited drying. Both cases have been reported in literature, [5,10] however the reason for the difference in drying behaviour has not been discussed.…”
Section: Resultsmentioning
confidence: 95%
“…In contrast, 2×2 electrode initiated exponential drying kinetics (falling drying rate), which indicates diffusion-limited drying. Both cases have been reported in literature, [5,10] however the reason for the difference in drying behaviour has not been discussed.…”
Section: Resultsmentioning
confidence: 95%
“…The ion current is small, in the order of a few milliamps per meter of wire. Previous experimental studies (Martynenko and Zheng, 2016;Singh et al, 2017) reported slightly lower currents (below 1 mA), which are most likely related to shorter wires or needle electrodes that were used. A quadratic relation between ion current and emitter voltage is found, in correspondence with previous studies (Dalvi-Isfahan et al, 2016;Martynenko and Kudra, 2016).…”
Section: Impact Of Geometrical Parameters and Operating Conditions On Airflow And Heat Transfermentioning
confidence: 85%
“…Typically only crossflow air speeds, generated mechanically with a fan, are reported in the case of hybrid fan-assisted EHD drying. Instead, analytical predictions are used to estimate the corona wind speed, based on the bulk electric field strength E b [30,44,53]:…”
Section: Air Velocitymentioning
confidence: 99%
“…Although the voltage is in the kV range, the corona ion current is often very low, in the mA range [44,52,53]. Thereby, the power required for the corona discharge P EHD is quite low, typically 1-10 W (Figure 2), which is in the same range as a computer fan.…”
Section: Energy Consumptionmentioning
confidence: 99%